"THE CHALLENGES OF TEACHING ENGLISH TO INTERNATIONAL STUDENTS" (Scientific journal of the Fergana State University, 2025)
In this article it is cleared some ideas about the problems and their types that arise during the teaching of English to international students. It also explains how to solve these problems and some steps you can take to overcome the difficulties.